Representations of traffickers in official UK discourse: examining the least known component of the human trafficking equation - Gaitis, Konstantinos Kosmas (International journal of law, crime and justice, 2023)
Through a framework that combines literature's observations on traffickers' policy-based representations with International Relations (IR) theories, this paper explores the representations of traffickers and anti-trafficking government goals in policies of the United Kingdom's (UK), Scottish and Northern Irish governments. Policies were found to mostly subscribe to a Realist's viewing of human trafficking, emphasising criminal choices. Still, and despite their growing tendency to focus on a wider range of traffickers, their dominant narrative tends to revolve around trafficking stereotypes, often ignoring the full spectrum of traffickers' identities to promote total human trafficking elimination. This discourse may overstate Britain's trafficking problem, sustaining state legitimacy and intervention and narrowing down the scope of anti-trafficking efforts. Conclusively, to ensure a more effective anti-trafficking response, the UK needs to set more feasible goals and based on an in-depth knowledge of traffickers strive to further enrich the policy-promoted human trafficking narrative.